PENGARUH PEMBERDAYAAN DAN SISTEM INFORMASI TERHADAP KINERJA PEGAWAI PADA PT. JASA RAHARJA(Persero) CABANG SULAWESI TENGAH - Rahmadian, Wahyudi (Katalogis, 2014)
This research aims to know and analyze the effect of empowerment and information system variables, simultaneously and partially on employee’s performance at PT. Jasa Raharja (Persero) Central Sulawesi. The Population of the research was the Officers at PT. Jasa Raharja (Persero) Central Sulawesi Officer were 31 persons. Analysis method used in this research is Multiple Linear Regression. Based on The data analisys, regression equation shows that Y =  0,281 +  0,775X1 + 0,261X2. The results show that Empowerment and Information System simultaneously performs positive  and  significant  effect  on  the  performance  Officers.  Partially,  empowerment  performs positive and significant effects on officers performance with regression coefficient of 0,775; information  system  performs  positive  and  significant  effects  on  officers  performance  with regression coefficient off 0,261.  Determination coefficient wich is indicated by adjusted R-Square 0,724 indicated that 72,40% lecturer’s performance has been effected by empowerment and information system, meanwhile the rest has been effected by other variables wich are not investigated in this research.